Implementasi Kurikulum 2013 dalam Pembelajaran Pendidikan Agama Islam (Studi Kasus di SMKN 1 Gesi dan SMKN 2 Sragen Kabupaten Sragen)Tahun Pelajaran 2016/2017 - , Yanto, Dr. Abdullah Aly, M.Ag, Dr. Mohamad Ali, S.Ag, M.Pd (2017)
This study elaborated on the implementation of the curriculum 2013 in PAI learning that took place in SMK N 1 Gesi and SMK N 2 Sragen in the academic year 2016/2017. This study has the main goal to obtain valid information about: 1) know the planning of curriculum implementation in 2013 in PAI learning in SMK N 1 Gesi and SMK N 2 Sragen Sragen; 2) investigate the implementation of the curriculum 2013 in PAI learning of SMK N 1 Gesi and SMK N 2 Sragen Sragen; 3) determine the evaluation / assessment of curriculum 2013, PAI learning in SMK N 1 Gesi and SMK N 2 Sragen; 4) complexion in PAI learning of SMK N 1 Gesi and SMK N 2 Sragen. The method used is descriptive qualitative, the research procedure that produces descriptive data in the form of words written or oral, and research is needed so that it can be observed that done in real life and real. While collecting data using interviews, observation and documentation and validity of the data. The main source of this research are the principal as school managers and teachers of Islamic education. The process of presenting data using descriptive naturalistic approach, which presents various objective conditions found in the field on various matters related to the implementation of learning Islamic religious education in SMK. Based on the results of this study concluded that; 1) at SMK N 1 Gesi and SMK N 2 Sragen has been implementing the curriculum in 2013 in the learning PAI start of the school year 2013/2014 but to SMK N 1 Gesi only lasted one semester and continues starting in 2016/2017 2) in the learning activities of teachers PAI divide into three stages: First, the preparation phase by making prota and promissory notes, syllabi and lesson plans. Second, the implementation phase as the core stage in the learning process. In the delivery of core content subjects PAI teacher SMK N 1 Gesi more dominant in lecture mode. Third, the stage of evaluation / assessment that teachers are grading system refers to the assessment standards in the curriculum of 2013, which include: cognitive (knowledge), affective (attitude) and psychomotor (skills) as well as the reporting of test results (the test), but not all the votes we can carry with a maximum, a fourth complexion in PAI of SMK N 1 Gesi more use lecture and question and answer and in SMK N 2 Sragen has been using active learning methods.